The Neurocognitive Architecture of Qur’anic Memorization: Synthesizing Working Memory and Memory Consolidation Mechanisms - Ary Asy’ari; Eva Latipah; Suyadi Suyadi (LP. Ma'arif Janggan Magetan, 2026)
This systematic review synthesizes 13 studies on Qur'anic memorization through cognitive neuroscience. Using PRISMA-guided screening of Scopus and PubMed records, the study identifies three taxonomic clusters: working-memory gating, consolidation-support strategies, and contextual-spiritual modulation. The findings show that Qur'anic memorization depends on attention control, phonological rehearsal, semantic linking, rhythmic repetition, multisensory encoding, muraja'ah-based retrieval, and cognitive load control. The review proposes a Neuro-Tahfidz model that connects sacred verbal input, working-memory regulation, memory consolidation, Islamic learning context, and instructional design. Its novelty lies in translating tahfidz as a theological-practical tradition into an empirical neuroeducational synthesis. It also extends memory theory beyond common Western language stimuli by focusing on a rhymed, repetitive, non-Western sacred text. The model remains conceptual because the reviewed studies use varied designs and limited direct neurocognitive measurements. The synthesis is therefore useful as a theoretical guide, not as a final causal claim. Future research should test the model experimentally across age groups, pesantren settings, and tahfidz learning methods.